Generating mutually unbiased bases and discrete Wigner functions for three-qubit system - Aliakbarzadeh, Mojtaba; Zainuddin, Hishamuddin (Institute for Mathematical Research, Universiti Putra Malaysia, 2014)
It is known that there exists 2N+ 1 mutually unbiased bases for N qubits system. Between the different MUB construction algorithms of the three-qubit case, we focus on Wootters method with discrete phase space that leads naturally to a complete set of 2N+ 1 mutually unbiased bases for the state space. We construct discrete Wigner function using mutually unbiased bases from the discrete phase space for three-qubit system by explicitly calculating the Wigner functions for exemplary three-qubit pure states such as the GHZ state, the W state and the embedded Bell state. We also highlight some quasi-probability characteristics of these entangled states.